Hospitality market in the Russian Federation: Present and trends - Tatyana N. Safronova; Tatyana L. Kamoza; Olga M. Evtukhova; Milena A. Khaneeva; Anastasia I. Vanchikova (Наука Красноярья)
The global socio-political and economic situation directly affects the tourism industry – the structure of tourist traffic is changing, new players are acquiring leading positions in the tourism market, a number of regions and countries are reorienting their economic activity to tourism, putting it in priority, other types and formats of travel are emerging. Over the past three years, the configuration of the tourism and hospitality market in Russia has faced significant changes, which is due to the transformation of international economic and political relations. Based on the analytical processing of quantitative information describing the macro level, key obstacles to the growth of the hotel industry have been identified, and current directions for its promotion have been determined.